PTU-054 Therapeutic Monitoring of TNF-Alpha Inhibitors in Crohn's Disease; Impact of Nice 2016 Guidelines in a UK District General Hospital. (17th August 2016) - Harrison, E; Padmanabhan, H; Shah, A; Murugananthan, A; Steed, H; Brookes, M
Abstract : Introduction: Therapeutic anti-TNFα monitoring enables optimisation of anti-TNFα therapy. Recently, NICE supported therapeutic monitoring of TNFα inhibitors in patients with Crohn's disease who fail to respond. However, NICE found the evidence for routine monitoring in patients responding adequately to be insufficient. Small studies show high Infliximab (INF) trough levels and low antibody levels to be associated with successful maintenance of remission. Methods: A retrospective review of drug level monitoring in patients with Crohn's disease taking anti-TNFα drugs was conducted. Patient demographics, IBD type, duration and distribution were recorded. Data were collected to compare against the NICE guidance (DG22). Trough levels, antibody presence and the use of concomitant immunosuppression (thiopurine and/or methotrexate) were noted. Any clinical impact of monitoring was recorded. Results: Over 26 months monitoring was performed 93 times in 80 patients. 60% of all monitoring was clinically indicated in patients suspected to be non-responders. The remaining 40% were part of routine care. Of the 80 patients, 53% were male. Median age at first monitoring was 36 years (range 17–79). Median time from diagnosis of Crohn's was 86 months (range 5–528). 26% had ileal, 30% had colonic and 44% had ileocolonic disease. 30% had stricturing and 8% had penetrating disease phenotypes. 39% had perianal disease. At diagnosis, 19% were aged 16 or below, 56% were aged 17 to 40 and 24% were aged over 40. Onset was unknown in 1%. For all drug monitoring, the median time from anti-TNFα initiation (59% INF; 41% Adalimumab (ADA)) was 60 weeks (range 6–470). 31% had concomitant immunosuppression. Antibodies were detected in 16% (22% INF; 8% ADA). Overall, as a result of monitoring, 49% continued their current anti-TNFα, 37% dose-escalated, 1% de-escalated, 8% stopped, 3% switched to ADA, 1% switched to INF and 1% changed to Vedulizumab. 13% started or increased thiopurine or methotrexate and 8% proceeded to surgery. Of those patients monitored as a part of routine care, 24% dose-escalated, 11% stopped anti-TNFα drugs and 5% switched to ADA. Doses were unchanged in 60%. Conclusion: A large proportion of monitoring in our population was for the routine evaluation in patients on anti-TNFα drugs. These patients are now considered outside of NICE practice guidelines. Thus, adhering to NICE guidelines will lead to a substantial reduction in the number of our patients tested. However, in this group, the evaluation of drug levels influenced care in 40% of cases. Thus, further studies are needed to determine the benefits of routine drug level monitoring in stable patients on anti-TNFα drugs. Disclosure of Interest: None Declared